The Analysis of Local Potential in BUM Desa Empowering in Desa Lembengan, Kecamatan Ledokombo, East Java - Dwi Hastuti; Nurwahdatul Chilmy (Jurnal Ilmu Sosial Mamangan, 2017)
This research examines to know empowerment effort by local government. It focuses on social capital in society and new local potentials. This study use descriptive qualitative research. This research uses some data collection techniques such as observation, in depth interview, and documentation. Data are conducted through stages such as (1) data reduction, (2) presentation of data, (3) conclusion. The results through these stages can be credible. Then data triangulation technique is used during validation. This research result shows that empowerment of BUM Desa still less successful. In progress and implementation, BUM Desa in Lembengan in 2010-2017 has not contributed to local governance income significantly. This research finds the weak role of social capital of society such as commitment, trust, norm, social network to support BUM Desa empowerment in Lembengan. There are some BUM Desa business partners as new local potential that can be developed such as brick industry, petulo cracker industry, and tobacco industry.Â